2015
DOI: 10.1016/j.bbamem.2014.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-assisted functional reconstitution of human P-glycoprotein (ABCB1) in giant liposomes

Abstract: This paper describes the formation of giant proteoliposomes containing P-glycoprotein (P-gp) from a solution of small proteoliposomes that had been deposited and partially dried on a film of agarose. This preparation method generated a significant fraction of giant proteoliposomes that were free of internalized vesicles, making it possible to determine the accessible liposome volume. Measuring the intensity of the fluorescent substrate rhodamine 123 (Rho123) inside and outside these giant proteoliposomes deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 72 publications
1
19
1
Order By: Relevance
“…GUVs containing proteins, was a very challenging task. Several protocols have been proposed 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26 , mostly based on the ones established for protein-free GUVs. All these approaches have been successfully used with specific proteins.…”
Section: Introductionmentioning
confidence: 99%
“…GUVs containing proteins, was a very challenging task. Several protocols have been proposed 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26 , mostly based on the ones established for protein-free GUVs. All these approaches have been successfully used with specific proteins.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated that the inhibitor driven MRP transporter inactivation results in increased mortality at least for two inhibitors, of the nematodes to Bcc strains, supporting the role of these transporters in Bcc infection. Verapamil has been characterized as a competitive inhibitor in ABCB1 malignant cell overexpression [ 52 ] as wells as a potent ABCC family inhibitor [ 53 ]. It is also involved in inhibiting C .…”
Section: Resultsmentioning
confidence: 99%
“…Hybrid lipid/polymer vesicles could be obtained via electroformation on Pt wires and ITO plates when using the lower voltage of lipids (3 V) . Both electroformation and gel‐assisted hydration showed that SUVs, in particular proteoliposomes, could be used as a substitute for the lipidic film to obtain proteoliposome GUVs with good reconstitution of transmembrane proteins …”
Section: Comparison Of the Different Methodsmentioning
confidence: 99%
“…GPCRs are omnipresent in human cells, mediating extracellular signals for physiological signaling. Alternatively, proteoliposome GUVs can also be generated from the proteoliposome SUVs like for electroformation with replacing the lipid film with the SUVs . P‐glycoprotein, a member of transporters using ATP found in prokaryotes and eukaryotes, was successfully reconstituted in liposome GUVs.…”
Section: Gel‐assisted Hydrationmentioning
confidence: 99%